Heterogeneous distribution of dopamine D2 receptor mRNA in the rat striatum: a quantitative analysis with in situ hybridization histochemistry. - Szele, F; Artymyshyn, R; Molinoff, P; Chesselet, M (1991)
Dopamine D2 receptor mRNAs have recently been cloned and their gross distribution in the central nervous system described. Quantitative in situ hybridization histochemistry with a cRNA probe complementary to the mRNAs encoding approximately 70% of the third intracellular loop of the rat D2 receptor was performed on sections of rat brain to determine whether differences previously observed in the density of ligand binding sites in subregions of the striatum were related to differences in mRNA levels. Film autoradiographic analysis demonstrated 30% more hybridization signal in the lateral compared to the medial caudate-putamen, a distribution parallel to that of binding of ligands specific for the D2 receptor. Inspection at the cellular level using emulsion autoradiography also indicated a differential distribution of the D2 receptor mRNA. Fewer positively labelled cells, as well as fewer silver grains per cell, were seen in the medial compared to the lateral half of the striatum. This suggests that the gradient seen in autoradiographic studies of the distribution of D2 receptors is related both to regional differences in D2 mRNA levels and to the density of cells expressing the receptor. In addition, the distribution of cells expressing D2 receptor mRNA in the extrastriosomal matrix was compared to that in striosomes identified by the presence of a high density of 3H-naloxone binding sites. Labelled cells were mainly found in the matrix (3H-naloxone binding-poor) but were also seen in striosomes (3H-naloxone binding-rich). The results suggest that differences in levels of D2 binding sites in subregions of the striatum are related to differences in the level of expression of this receptor in intrinsic striatal neurons, suggesting differential regulation of dopamine D2 receptor gene expression in topographically distinct striatal neurons.